The potential of local orange peel-derived eco-enzymes in producing indole acetic acid - Siska Alicia Farma; Nurfa Dewiza Luzik; Salma Sakina; Irma Leilani Eka Putri; Linda Advinda; Azwir Anhar (Acta Biochimica Indonesiana)
Background: Ecoenzymes, created from the fermentation of organic citrus waste, offer a sustainable method to produce Indole Acetic Acid (IAA), a phytohormone vital for plant growth. This study investigates the potential of these ecoenzymes in promoting sustainable agriculture.